Estudo do efeito da adição de Au, Pd e Pt em catalisadores Cu/CeO2 aplicados à reação de deslocamento gás-água a baixa temperatura - Silva, André Leopoldo Macêdo da (Universidade Federal de São Carlos, 2008)
Cu/CeO2 catalysts doped with Au, Pd or Pt (WGSR) were prepared and applied in water gas shift reaction. The CeO2 support was prepared by four different way: urea co-precipitation-gelation (CeO2-UGC), hydrothermal method (CeO2-HT), precipitation with NH4OH (CeO2-P) and Pechini method (CeO2-Pe). The CeO2-ZrO2 oxide was prepared by Pechini (CeO2-ZrO2-Pe). The Cu deposition was performed by deposition-precipitation on CeO2- UGC, CeO2-HT and CeO2-P (3, 5 or 10wt% Cu/CeO2) and by impregnation on CeO2-Pe and CeO2-ZrO2-Pe. The Au, Pd and Pt (0,2, 0,5 or 0,8wt%) deposition was made by deposition-precipitation. The supports and supported catalysts were characterized by X ray diffraction (XRD), BET specific surface area, X ray energy dispersive spectroscopy (EDS), temperature programmed reduction (TPR), X ray photoelectron spectroscopy (XPS), electronic transmission microscopy (TEM), temperature programmed reduction with dispersive X-ray absorption spectroscopy (TPR-DXAS) and temperature programmed oxidation (TPO). The catalysts were tested in low-temperature water-gas shift reaction and the products were analyzed online by gas chromatography. The results showed that the addition of ZrO2 to CeO2 avoided the decrease of specific surface area of support. The CeO2-P support presented the higher specific surface area. The addition Au, Pd or Pt increased the activity of the catalysts with lower amount metal (< 3,0 wt%). In the catalysts with metal amount higher than 0,5 wt% only the Pd promoted catalysts showed the same or higher activity than copper catalysts. The bimetallic catalysts presented diverse behaviors. In the catalysts with Au the activity decreased with the increase of Au amount. On the other hand, the catalysts with Pd presented opposite performance, with the activity increasing when Pd amount increases. The Pt promoted catalysts do not showed activity changes with increase of Pt amount. The Pd showed the best performance among the materials tested as monometallic catalyst or as promoter in the copper catalysts.
Keywords: Catálise heterogênea; Hidrogênio como combustível; Catalisadores bimetálicos; Metais nobres; Catalisadores de cobre; CeO2; ENGENHARIAS::ENGENHARIA QUIMICA